Histology-specific FGFR2 alterations and FGFR2-TACC2 fusion in mixed adenoid cystic and neuroendocrine small cell carcinoma of the uterine cervix - Corey M. Gill; Theofano Orfanelli; Lorene Yoxtheimer; Christine Roy-McMahon; Jessa Suhner; Shannon Tomita; Tamara Kalir; Yuxin Liu; Jane Houldsworth; Valentin Kolev (Elsevier, 2020)
Neuroendocrine small cell carcinoma of the uterine cervix portends a dismal prognosis with limited treatment options. Rarely, tumors of mixed-lineage appear in gynecologic malignancies. Here, we report a 77-year-old woman who presented with complete uterine prolapse and 4-month history of vaginal bleeding. Histopathologic evaluation revealed a mixed adenoid cystic carcinoma and neuroendocrine small cell carcinoma of the uterine cervix. The tumor was PD-L1 and HPV 35 positive. The patient was treated with up-front surgery and adjuvant radiation. Independent, histology-specific alterations in FGFR2 and a FGFR2-TACC2 fusion were identified. Progression of disease occurred within 6 months for which she received chemotherapy and immunotherapy. However, the patient expired within a year. We comprehensively review how screening for and targeting of FGFR alterations in recurrent and metastatic cervical cancer might serve as a touchstone for future treatment regimens.